Analysis of Functional Position Preferences for Procurement Managers Based on Perception, Potential, Motivation, and Interest Using Fishbone Diagrams - So'immawati, S.; Sunarno, AG; Sumekar, Kertati (Manunggal Halim Jaya, 2025)
This study aims to identify and analyze the causes and effects of the preferences of the Functional Position of Goods / Services Procurement Manager (JF PPBJ) reviewed from the perspective of perception, potential, motivation and interest using Fishbone analysis in an effort to improve the Functional Position of Goods / Services Manager at the Regional Secretariat of Rembang Regency. The lack of the number of goods/services procurement managers has resulted in the fulfillment of the elements of professionalism of goods / services procurement managers in the form of human resources implementing goods and services procurement in this case JF PPBJ has not been optimal and fulfilled. This study uses a qualitative approach with data collection techniques in the form of interviews, observations, and documentation. The research informants involved by the researcher were 15 (fifteen) people. The results of this study indicate that things that can be done to meet the needs of the Functional Position of Procurement Manager of Goods and Services are by implementing a renaksi (action plan) for fulfilling JF PPBJ until at least 60% of the needs are met through the first appointment , namely the Civil Servant Candidate (CPNS) acceptance path, appointment from other positions in the form of appointment of Civil Servants (PNS) from other positions into JF PPBJ (position transfer), increasing competency tests or functional training organized by the Government Goods / Services Procurement Policy Institute (LKPP) as the JF PPBJ Supervisory Agency, the existence of guarantees and certainty from the Regional Government to design legal protection (ranperkada) related to JF PPBJ, providing additional income to improve the welfare of JF PPBJ, implementing the procurement process of goods/services according to procedures to mitigate risks related to the law, and maintaining JF PPBJ so that it is not transferred because in terms of maturity it will have an impact on the decline in the ITKP ratio value (Governance Index). With these efforts, the Procurement of Goods and Services Section of the Rembang Regency Secretariat is able to fulfill the elements of procurement professionalism in the form of human resources implementing the procurement of goods/services in this case, JF PPBJ and contribute to providing better services to the community.